Development of Multiply Card as Multiplication Learning Media in Elementary Schools - Evi Faujiah; Herlina Usman; Achmad Khomsin; Vina Shelfiana (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
This study aims to develop the Multiply Cards game as a medium for learning mathematics in additional material in elementary schools that is interesting, metacognitive, and connection-based. This type of research is research and development (R&D) according to the ADDIE development model which consists of five stages, namely: analysis, design, development, implementation, and evaluation. The subjects of this study were class students at SDN Mekarsari 5, Kec II.Cimanggis, Depok City. The research tools consisted of material expert validation instruments, media expert validation instruments, teacher validation instruments, and student and teacher response questionnaires. Based on the evaluation of the validity test, the validation results of the material experts were considered "very feasible" with a total of 85% and the results of the media expert validation were 89%, while the teacher's validation was obtained with a total of 81%. So it can be concluded that the development of the Multiply Cards game as a medium for increasing learning in elementary schools is categorized as "very likely". This means that the media developed by the researcher can be used as a learning medium for arithmetic operations in elementary schools.